2014
DOI: 10.1016/j.infsof.2014.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Potential and limitations of the ISBSG dataset in enhancing software engineering research: A mapping review

Abstract: Context: The International Software Benchmarking Standards Group (ISBSG) maintains a software development repository with over 6,000 software projects. This dataset makes it possible to estimate a project"s size, effort, duration, and cost. Objective: The aim of this study was to determine how and to what extent, ISBSG has been used by researchers from 2000, when the first papers were published, until June of 2012. Method: A systematic mapping review was used as the research method, which was applied to over 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…3.00 and background management authority settings To provide our clients a set of complete advanced function and good user experience vehicle-mounted recreational and multimedia system. 7.00 To develop a universal interface module based on Modbus communication agreement, makes each isomerous station can be connected.…”
Section: Product Description Effortmentioning
confidence: 99%
“…3.00 and background management authority settings To provide our clients a set of complete advanced function and good user experience vehicle-mounted recreational and multimedia system. 7.00 To develop a universal interface module based on Modbus communication agreement, makes each isomerous station can be connected.…”
Section: Product Description Effortmentioning
confidence: 99%
“…Lokan et al [32] position ISBSG as a 'low cost initial determination of an organization's industry position and its comparative strengths and weaknesses'. Fernández-Diego et al [33] inventoried the use of the ISBSG-repository by performing a systematic mapping review on 129 research papers. They found that in 70,5% of the studies prediction of effort is the main focus.…”
Section: Threats To Validitymentioning
confidence: 99%
“…The most common research topic when the ISBSG data set has been used is prediction methods with 70.5%. This percentage was obtained from 129 studies published between years 2000 and 2012 in 19 journals and 40 conferences [33].…”
Section: ) Genetic Algorithms Have Only Been Used In Combination Withmentioning
confidence: 99%